No sweatshop label at hunter gatherer change management at the Brotherhood of St. Laurence. - McAuliffe, Marc; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2002)
In 1999 Father Frances was appointed Executive Director of the Brotherhood of St. Laurence in Melbourne.This program identifies the radical changes that occurred with his appointment. Provides an overview of social entrepreneurs, triple bottom line and globalisation. Focuses on Hunter Gatherer, a social enterprise which embodies the new direction taken by the Brotherhood
Title from title screen
DVD format
Keywords: Brotherhood of St. Laurence -- Case studies; Organizational change -- Victoria -- Case studies; Hunter Gatherer -- Case studies; Charities -- Victoria -- Case studies